ERP implementation in hospitals: a case study. (18th October 2012) - Agarwal, Divya; Garg, Poonam
In a competitive healthcare sector, hospitals have to focus on their processes in order to deliver high–quality care while at the same time reducing costs. Many hospitals have decided to adopt one or another Enterprise Resource Planning (ERP) system to improve their businesses, but implementing an ERP system can be a demanding endeavour. The systems are so difficult to implement that some are successful; many have failed, causing multimillion dollar losses. The challenge of ERP solutions lie in implementation because they are complex, time consuming and expensive too. This paper describes the various process workflows and phases of ERP implementation at Fortis Hospital Cunningham Road, Bangalore, India. This knowledge will provide valuable insights for the researchers and practitioners to understand the different process workflows and to make informed decisions when implementing ERP in any hospital.